2021
DOI: 10.1001/jamainternmed.2021.1408
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Educational Intervention for Patients With Uninvestigated Dyspepsia Referred for Upper Gastrointestinal Tract Endoscopy

Abstract: IMPORTANCE Diagnostic yield of upper gastrointestinal (GI) tract endoscopy for uninvestigated dyspepsia is low, and its clinical implications are limited. There is an unmet need for better strategies to reduce the volume of upper GI tract endoscopic procedures for dyspepsia.OBJECTIVE To study the effectiveness of a web-based educational intervention as a tool to reduce upper GI tract endoscopy in uninvestigated dyspepsia. DESIGN, SETTING, AND PARTICIPANTSThis open-label, multicenter, randomized clinical trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
0
18
0
1
Order By: Relevance
“…http://gut.bmj.com/ Gut: first published as 10.1136/gutjnl-2022-327737 on 7 July 2022. Downloaded from and was associated with similar improvements in symptoms and quality of life, compared with prompt endoscopy 127.…”
mentioning
confidence: 84%
“…http://gut.bmj.com/ Gut: first published as 10.1136/gutjnl-2022-327737 on 7 July 2022. Downloaded from and was associated with similar improvements in symptoms and quality of life, compared with prompt endoscopy 127.…”
mentioning
confidence: 84%
“…8,9 Nevertheless, some of these procedures could also have been superfluous and might not have needed to be performed. 10 In conclusion, we observed profound reductions in gastro enterological procedure volumes during the first wave of the COVID-19 pandemic. Procedure volumes returned to or increased above reference levels during subsequent phases of the pandemic, which is a testament to the resilience and creativity of gastroenterology departments across the nation.…”
Section: Effect Of the Covid-19 Pandemic On Procedures Volumes In Gas...mentioning
confidence: 63%
“…In a review of strategies used to reduce the use of upper GI endoscopy for dyspepsia, one of the most common inappropriate indications, the authors identified strategies for each of four targets: development and implementation of guidelines, clinical assessment using algorithm-based referral, testing for Helicobacter pylori , and offering treatment with a proton pump inhibitor or a histamine H 2 receptor antagonist 16. The results of a subsequent clinical trial suggested that at least web-based patient education is effective in reducing the need for upper GI endoscopy in uninvestigated dyspepsia 17…”
Section: Solutionsmentioning
confidence: 99%